PROTECTED BINARY IMAGE AND ITS PRODUCTION - HAWAADO JII SUKIRUDO; IRISU BII KEI BURUUMU; AGOTA EFU FUEHAABARI; RICHIYAADO EI MINZU; RATSUSERU EI GAUDEIANA (1994)
PURPOSE: To enable a protected image to be repeatedly cleaned using a solvent by separating a support from the image so that a durable layer remains bonded to the image and covering the image with the durable layer. CONSTITUTION: A durable layer is laminated adhesively to both first and second regions of an image 10b and thus remains stuck to the image 10b. Further, a support layer is separated from the image 10b so as to cover the image with the durable layer. The durable layer is constituted of a polymer organic material, into which siloxane is incorporated. In detail, a laminating sheet 30 is stripped from the image 10b by for example, gripping one end of the sheet 30 mechanically. Consequently, the peripheral part 32a of an adhesive layer and the peripheral part 34a of the durable layer remain connected to a peelable layer 36 and a support 38. Further, the center part 32b of the adhesive layer and the center part 34b of the durable layer remain connected to the image 10b.